The Effect of Arabica Coffee Extract ( Coffea Arabica L.) on the Progression of Lactobacillus Cervicovaginal Microbiome Biomarkers - Farisha Firzana; Humairah Medina Liza Lubis (International Journal Labs, 2025)
Cervical infection or cervicitis is an inflammation of the cervical epithelium that can progress to chronicity and potentially lead to cervical cancer. Lactobacillus crispatus, which is normal vaginal flora, can migrate to the cervix and cause inflammation. Mandailing arabica coffee (Coffea arabica L.) is rich in phenolic compounds and antioxidant activity, with antibacterial potential. This research aims to assess the effect of Mandailing arabica coffee (Coffea arabica L.) extract on the growth of Lactobacillus crispatus as an effort to reduce the progression of cervicovaginal microbiome biomarkers. This laboratory experimental study used a completely randomized design (CRD) with 25%, 50%, and 100% concentrations of Mandailing arabica coffee extract. The antibacterial activity test was carried out by liquid dilution, solid dilution, and disc diffusion methods. Data were analyzed using a one-way ANOVA test followed by the Least Significant Difference post hoc test. Mandailing arabica coffee extract contains alkaloids, flavonoids, saponins, tannins, and triterpenoids. Liquid and solid dilution tests showed inhibition of Lactobacillus crispatus growth at all extract concentrations. The disc diffusion test produced the greatest average inhibition at 100% concentration (6.62 cm), followed by 50% (5.19 cm), and 25% (4.81 cm). ANOVA analysis showed a significant effect of extract administration on the growth of Lactobacillus crispatus (p < 0.001). Mandailing arabica coffee (Coffea arabica L.) extract has antibacterial activity against Lactobacillus crispatus, with growth inhibition increasing alongside increasing extract concentration. This indicates the potential of Mandailing arabica coffee in preventing cervical inflammation and the progression of precancerous lesions.